2006
DOI: 10.2190/p00l-2061-461x-336q
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking, Friendship Factors, and Social Norm Perceptions among Central and Eastern European High School Students

Abstract: Studies investigating smoking behavior among adolescents living in post-communistic Central-European countries are sparse. This study focused on the relationship between cigarette smoking, certain friendship factors, and social norm perceptions among 1,886 Central-Eastern European adolescents from high schools in Hungary, Slovakia, Czech Republic, and Romania. Smoking behavior was related to having friends who smoke, ease or difficulty making new friends, time spent with friends after school and during evening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…An important aspect of this research was to determine normative beliefs about smoking in a sample of Hungarian students. Previous research in North American and Central‐Eastern European youth has found that youth tend to highly overestimate the perceived prevalence of smoking among their peers, 15,28,29 and we found this also to be the case in the current sample. The Hungarian students estimated that 78.6% of 12th graders were current smokers.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…An important aspect of this research was to determine normative beliefs about smoking in a sample of Hungarian students. Previous research in North American and Central‐Eastern European youth has found that youth tend to highly overestimate the perceived prevalence of smoking among their peers, 15,28,29 and we found this also to be the case in the current sample. The Hungarian students estimated that 78.6% of 12th graders were current smokers.…”
Section: Discussionsupporting
confidence: 72%
“…Perceived prevalence of smoking, however, was not independently associated with current smoking, susceptibility to future smoking, or ever tried smoking. This finding was unexpected because a previous study of Central and Eastern adolescents found that adolescents who overestimated smoking by their peers were at increased risk of smoking 29 . Because the overestimation of smoking is often associated with youth smoking, youth smoking programs often aim to lower or correct misperceptions of the prevalence of smoking.…”
Section: Discussionmentioning
confidence: 93%
“…Smoking prevalence for Hungarian, Slovakian, Romanian, and Czech Republic students was reported earlier in this journal (Page et al, 2006). difference in Table 4 on hopelessness remained significant.…”
Section: Notesupporting
confidence: 68%
“…Indeed, a consistent and dramatic pattern of misperceptions about peer norms for substance use has been documented in studies conducted in several nations (Hughes, Julian, Richman, Mason, & Long, 2008;Kilmer et al, 2006;Lintonen & Konu, 2004;McAlaney & McMahon, 2007;Page, Ihasz, Hantiu, Simonek, & Klarova, 2008;Page, Ihasz, Simonek, Klarova, & Hantiu, 2006;H. W. Perkins, 2007;H.…”
Section: Misperceived Norms and The Social Norms Approach To Reducingmentioning
confidence: 82%